2003
DOI: 10.1103/physrevlett.90.248303
|View full text |Cite
|
Sign up to set email alerts
|

Pump-Probe Photoionization Study of the Passage and Bifurcation of a Quantum Wave Packet Across an Avoided Crossing

Abstract: The application of femtosecond pump-probe photoelectron spectroscopy to directly observe vibrational wave packets passing through an avoided crossing is investigated using quantum wave packet dynamics calculations. Transfer of the vibrational wave packet between diabatic electronic surfaces, bifurcation of the wave packet, and wave packet construction via nonadiabatic mixing are shown to be observable as time-dependent splittings of peaks in the photoelectron spectra. DOI: 10.1103/PhysRevLett.90.248303 PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Multiconfiguration schemes, such as Tully's surface hopping, are in general required to account for bifurcation paths with entaglement [45,46]. Although the undeniable success of these mixed approaches to describe many nonadiabatic phenomena, some limitations arise when quantum nuclear effects such as tunneling [47], decoherence [48] or interferences [49] occur. Only the so-called quantum wave packet methods [50][51][52] provide a complete description of nuclear quantum effects, although their computational cost becomes rapidly unaffordable with the size of the system.…”
Section: Nonadiabatic Molecular Dynamicsmentioning
confidence: 99%
“…Multiconfiguration schemes, such as Tully's surface hopping, are in general required to account for bifurcation paths with entaglement [45,46]. Although the undeniable success of these mixed approaches to describe many nonadiabatic phenomena, some limitations arise when quantum nuclear effects such as tunneling [47], decoherence [48] or interferences [49] occur. Only the so-called quantum wave packet methods [50][51][52] provide a complete description of nuclear quantum effects, although their computational cost becomes rapidly unaffordable with the size of the system.…”
Section: Nonadiabatic Molecular Dynamicsmentioning
confidence: 99%
“…We also report the photoelectron angular distributions for these timeresolved spectra. We have previously demonstrated the utility of such time-resolved photoelectron angular distributions and the need to incorporate geometry-and energy-dependent photoionization matrix elements in studies of time-resolved photoelectron spectra in a series of papers tracking funda-mental wavepacket dynamics in different scenarios: vibrational motion across a one-dimensional double-well potential in an excited state of Na 2 , [24][25][26][27][28] wavepacket bifurcation at an avoided crossing in NaI, 29,30 and proton transfer in the ground state of chloromalonaldehyde. [31][32][33] The scheme for our studies of the pump-probe photoelectron spectra in NO 2 is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our formulation of time-resolved pump-probe photoelectron spectroscopy has been fully discussed in earlier papers 24,28 and here we present just a brief outline with emphasis on the use of geometry-and energy-dependent photoionization matrix elements. The wavefunction of the total system, C(r,R,t), is expanded in the electronic wavefunctions relevant to the pump-probe arrangement,…”
Section: Time-resolved Photoelectron Spectroscopymentioning
confidence: 99%
“…In fact, internal conversion in polyatomic molecules was among the earliest suggested application of this technique, 21 which was subsequently realized experimentally. 22 We have also previously demonstrated the utility of time-resolved photoelectron spectra, along with the need to incorporate geometry-and energy-dependent photoionization matrix elements in such studies, in a series of papers tracking wavepacket dynamics in different scenarios: vibrational motion across a one-dimensional double-well potential in an excited state of Na 2 , [23][24][25][26][27] wavepacket bifurcation at an avoided crossing in NaI, 28,29 and proton transfer in the ground state of chloromalonaldehyde. [30][31][32] Anticipating that advances in ultrashort pulse shaping technology may also well enable the observation of wavepacket dynamics through a CI on the actual time scale of the nonadiabatic transition, we recently studied the photoelectron energy and angular distributions expected in and around the CI between the lowest 2 A 0 states of the NO 2 molecule 33,34 and showed that the photoelectron signals, particularly the angular distributions, provide a valuable window on wavepacket dynamics there.…”
Section: Introductionmentioning
confidence: 99%